Efeitos do método pilates no controle da dor em mulheres com fibromialgia: uma revisão sistemática - Oliveira, Melquisedek Monteiro de (2021)
Introduction: Fibromyalgia (FM) is a disease characterized by the presence of diffuse and chronic musculoskeletal pain, associated with symptoms such as fatigue, sleep changes, anxiety and depression. The practice of physical exercises has been recommended as one of the forms of treatment for patients with FM. In this context, the Pilates method can be considered an alternative for the treatment of FM. Objective: to investigate the effects of the Pilates method pain control in women with FM. Methods: This is a systematic review of randomized trials that use the Pilates method as an intervention protocol in the treatment of FM. The search was performed in LILACS, MedLine, PubMed, SciELO, CENTRAL and PEDro databases, including articles published from 2011 in English, Spanish and Portuguese. The sample consisted of women diagnosed with fibromyalgia and aged 18 years or over. The primary outcome was pain and as secondary outcomes the impact of FM, quality of life, anxiety and depression were obtained. Results: a total of 3095 studies were found, with only 11 articles being selected to be read in full after applying the eligibility criteria. Only four studies were included, published between 2016 and 2020. All participants in the groups that used the Pilates method as an intervention showed decreased pain and improved quality of life. Conclusion: it is possible to suggest that the Pilates method is an adjunctive alternative used in the treatment of FM, since the studies included in this review have shown good results in reducing symptoms in women with FM.